Crop-to-wild hybridization in cherries-Empirical evidence from Prunus fruticosa - Macková, Lenka; Vít, Petr; Urfus, Tomáš (Evolutionary applications, 2018)
Crop cultivation can lead to genetic swamping of indigenous species and thus pose a serious threat for biodiversity. The rare Eurasian tetraploid shrub Prunus fruticosa (ground cherry) is suspected of hybridizing with cultivated allochthonous tetraploid P. cerasus and autochthonous diploid P. avium. Three Prunus taxa (447 individuals of P. fruticosa, 43 of P. cerasus and 73 of P. avium) and their hybrids (198 individuals) were evaluated using analysis of absolute genome size/ploidy level and multivariate morphometrics. Flow cytometry revealed considerable differentiation in absolute genome size at the tetraploid level (average 2C of P. fruticosa = 1.30 pg, average 2C of P. cerasus = 1.42 pg, i.e., a 9.2% difference). The combination of methods used allowed us to ascertain the frequency of hybrids occurring under natural conditions in Central Europe. The morphological evaluation of leaves was based upon distance-based morphometrics supplemented by elliptic Fourier analysis. The results provided substantial evidence for ongoing hybridization (hybrids occurred in 39.5% of P. fruticosa populations). We detected homoploid introgressive hybridization with alien P. cerasus at the tetraploid level. We also found previously overlooked but frequent triploid hybrids resulting from heteroploid hybridization with indigenous P. avium, which, however, probably represent only the F1 generation. Although both hybrids differ in ploidy, they cannot be distinguished using morphometrics. Hybrids are frequent and may endanger wild populations of genuine P. fruticosa via direct niche competition or, alternatively or in addition, via introgression at the homoploid level (i.e., genetic swamping). The cultivation of cherries thus substantially threatens the existence of genuine P. fruticosa.
Keywords: Prunus; hybridization; crop‐to‐wild gene flow; absolute genome size; cherry; ploidy level; introgression